An Analytical Study Of The Relationship Between The Exported Goods And The Transformational Industry Sector While Implementing Free Trade In Syria (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Industry plays a major role in foreign trade, as the value of exports increases with the increase in the added value on exported goods. This is achieved in the Transformational industry, which highlights its importance in creating a strong industrial structure that enables the state to develop its production structure in order to achieve a highly competitive ability for its exports to compete in export markets.The study aimed to determine the impact of the economic blockade on the Syrian industrial sector during the post-war period and ended with developing a linear link formula to discover the relationship between the exported goods and the gross local production of the transformational industry sector using the SPSS statistical program during the period of trade liberalization that existed before the war.